Linguistic Inventiveness, Creativity, and Variation in Taufiq Rafat’s Poems: A Stylistic Study - Muhammad Haroon Jakhrani (Journal of Communication and Cultural Trends, 2023)
The current study attempted to analyze the poetic style of Taufiq Rafat. The study focused on Rafat's poetic originality, uniqueness, and grammatical inconsistencies. The qualitative, analytical, and theoretical aspects of this research were analyzed as well. In order to properly and efficiently conduct the study, only a handful of Rafat's poems were selected for analysis and the concentration remained solely on lexical level. The investigation focused on few specific poems of Rafat including Village Girl, Classmate, A Middle-Class Drawing Room, and Once Upon a Time.  Leech and Short (1981) models were used to comprehend Rafat's style and how expertly and artistically he handles language to accomplish his objectives and expectations. For academics interested in linguistic and stylistic analysis along with language element identification in any literary text, especially Rafat's poetry, this study is crucial. The study concluded that Rafat used relatively identical stylistic elements. Although, some similarity in the basic form of the poems resulted to deviations and innovations in a few verses while reflecting distinctive and diverse, different and unique meanings along with interpretations in each of his poems.